REGULASI ZAKAT MENURUT MAZHAB NEGARA DAN MAZHAB DAERAH (Studi Atas Undang-undang No. 23 Tahun 2011 Tentang Penglolaan Zakat dan Qanun Provinsi Nangroe Aceh Darussalam No 7 Tahun 2004 Tentang Pengelolaan Zakat dan Qanun Provinsi Nanggroe Aceh Darussalam No. 10 Tahun 2007 Tentang Baitul Mal) - Baroroh, Nurdhin (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
One of the pillars of Islam which must be fulfilled by the Muslims is topaying zakat. One element in the fulfillment of Zakat is Muzakki, or theperson who has to pay zakat on property held. In any form of impositionof Islam to his people (from the praying until Hajj obligation) is notmerely a form of obedience to the commands of Allah as an expression offaith alone or Hablun Min Allah, but there is other liability which cannot be – read: like two sides of the coin – the pious charity / HablunMin An-Naas. In the context of zakat, so that the obligation imposedon the Muzakki, an obligation that is’ Aini and even in Islamichistory, Sahabat Abu Bakr R.A. never enact permissibility to fight forMuslims who do not want to pay zakat. And than according with theconditions of the times, eventually every Islamic countries in the world,is also implementing regulations regarding zakat for each country, ofcourse, with the application of different between each of these countries.